Arsitektur Islam: Seni Ruang dalam Peradaban Islam - Fikriarini, Aulia (el Harakah: Jurnal Budaya Islam, 2010)
Human being as a caliph, here related to the function of architect, has responsibility for the environment. Hence, in doing their activities in this world, they have to cope with the nature considering the principal of balance and harmony. Architecture as one of the sciences should also go along with the Islamic values. The values based on the Quran should certainly be the foundation for all efforts of developing any sciences, including architecture. The application of Islam values will produce works of “Islamic architecture” that comprise a combination of culture and humans’ submission to their God, which characterizes the harmony of the human beings, environment, and their  Creator. Islamic architecture suggests a complex geometrical relation, hierarchy of shapes and ornaments, and deep symbolic meaning. This writing describes the fact that works of Islamic architectures in over the world that is based on Islamic ethical values and manners do not represent a single and identical shape. However, the varieties and wealth of shapes are unified by one purpose, that is, as a medium of devoting to God. The varieties create a multitude of Islamic architecture products within Islamic civilization, which lead human beings to rahmatan lil alamiin. Manusia sebagai khalifah, disini berhubungan dengan fungsi tanggung jawabnya terhadap lingkungan. Maka dalam melakukan aktivitasnya di dunia ini, mereka harus mengatasi alam dengan mempertimbangkan prinsip keseimbangan dan harmoni. Arsitektur sebagai salah satu ilmu juga harus sesuai dengan nilai-nilai Islam. Nilai-nilai yang berdasarkan pada Quran pastilah menjadi fondasi bagi semua usaha pengembangan ilmu apapun, termasuk arsitek. Penerapan nilai-nilai Islam akan menghasilkan karya-karya "arsitektur Islam" yang terdiri dari kombinasi antara kedaulatan budaya dan manusia dengan Tuhan mereka, yang mencirikan keharmonisan manusia, lingkungan, dan Penciptanya. Arsitektur Islam menunjukkan hubungan geometris yang kompleks, hierarki bentuk dan ornamen, dan makna simbolik yang dalam. Tulisan ini menggambarkan fakta bahwa karya arsitektur Islam di seantero dunia yang berlandaskan nilai etika dan tata krama Islam tidak mewakili bentuk tunggal dan identik. Namun, varietas dan kekayaan bentuk tidak ada satu tujuan, yaitu media untuk mengabdikan diri kepada Tuhan. Varietas tersebut menciptakan banyak produk arsitektur Islam dalam peradaban Islam, yang menyebabkan manusia menjadi rahmatan lil alamiin.